(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article examines the cognitive style of metaphorization as a specific mechanism of artistic expression, through which the figurative perception of the text is formed. Drawing on cognitive linguistics theories, the article analyzes the conceptualization processes underlying metaphorical thinking and explores their role in structuring the semantic space of a literary work. The study examines the features of metaphorical construction, including its multi-layered organization and its relationship with aesthetic perception. The results highlight the significance of integrating cognitive methods into literary analysis to deepen our understanding of linguistic and cultural practices. The relevance of the study lies in its examination of how a writer’s cognitive style influences the process of metaphorization in literary texts. Employing an interdisciplinary approach that integrates cognitive psychology, linguistics, and literary analysis, the study explores how cognitive processes shape metaphor interpretation. The study explores the mechanisms of conceptual formation, emotional resonance, and linguistic structuring. The main objective of the study is to explore and clarify the complex relationship between the writer’s cognitive style and the process of metaphorization in literary texts. By analyzing how individual cognitive differences affect the creation of metaphors, the study provides a deeper understanding of the interaction between thought processes and artistic expression. By linking cognitive styles with metaphorical structures, the study contributes to the development of a conceptual model. The article was prepared within the framework of the project BR21882249 “Improvement of the National Corpus of the Kazakh Language (NKKL) as a tool for intercultural communication and expansion of its subcorpora”. Keywords: metaphorization, cognitive style, mental picture, mentality, figurative words.